STUDY ON RAMAYANA COMPARISON - Shyam sundar Prasad (International Journal of Multidisciplinary Research and Studies, 2021)
Epic poetry is a very old kind of literature, and it may even be one of the very oldest forms. Epics are lengthy narratives that recount the exploits of heroic figures and otherworldly characters, such as gods. The tale invariably describes the heroic achievements of powerful monarchs, assistance from the gods, intrigues, battles between competing philosophies and morality, and unbeatable soldiers and their exploits. Epics feature a large cast of characters, including divine deities or gods, convoluted plots with many subplots and incidents, rhetorical elements that appeal to the morals and morality of people of all generations, and inspiration for humanity. Epics also serve as a source of motivation for people everywhere.